Stimulus Hafalan Al-Qur’an Melalui Seni Tilawah Pada Anak-Anak Di TPQ Nurul Iman Desa Tamaran Kecamatan Hinai Kabupaten Langkat - Nurhanifah, Nurhanifah; Wahyu Pradana, Kevin; Mahyiddin, Mahyiddin (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2024)
This study aims to determine the process of providing stimulus and to know the improvement of memorization through the art of recitation, the author uses a type of classroom action research (CAR) using a descriptive research methodology, namely research to provide data by describing certain symptoms. The results showed that the provision of stimulus through the art of recitations in memorizing Surah Al-Falaq verses 1-5, namely there were 3 responses, perceptual responses (cognitive), emotional responses (affective), behavioristic responses (behavior). Perceptual (cognitive) responses describe students more quickly imitating ustadz (teacher) in memorizing, and their memory power will not forget, emotional (affective) responses describe students when memorizing using the art of recitations not talking much with themselves or with their friends, and behavioristic responses (behavior). behavior) shows disciplined students with their presence, never absent. As for improving the memorization of Surah Al- Falaq through the art of recitation, namely before being given action, students are lazy to memorize, many forget to memorize, then makhrajul letters and tajwid are still lacking, in the first cycle of action only 6 people achieved completeness, namely getting 54.54 results. %. Then the author took action in the second cycle, in the second cycle the students' memorization mastery increased, namely there were 9 people who got mastery with a percentage of 81.81%. This proves that there is a change or increase in memorization in children at TPQ Nurul Iman, Tamaran Village, Hinai District, Langkat Regency through the art of recitation. Keywords: Art of Recitation, Improving Memorizing of the Qur'an